2018
DOI: 10.1111/btp.12528
|View full text |Cite
|
Sign up to set email alerts
|

Multiple signaling in a variable environment: expression of song and color traits as a function of ambient sound and light

Abstract: Many animals communicate using more than one signal, and several hypotheses exist to explain the evolution of multiple signals. However, these hypotheses typically assume static selection pressures, and previous work has not addressed how spatial and temporal environmental variation can shape variation in signaling systems. In particular, environmental variability, such as ambient lighting or noise, may affect efficacy (e.g., detectability/perception by receivers) of signals. To examine how signal expression v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
(208 reference statements)
0
4
0
Order By: Relevance
“…Per sensory drive model (Endler 1992), many environmental factors can influence colour-signal transmission and evolution, including water depth (Seehausen et al 2008) and vertical location in a forest (Endler 1993;Gomez & Thery 2004). Additionally, animals often interact with the environment by seeking out specific lighting conditions (Endler & Thery 1996;Heindl & Winkler 2003;Seehausen et al 2008;Cronin et al 2014;Simpson & McGraw 2018a) or orienting themselves in specific ways relative to the sun (Hamilton 1965;Rutowski et al 2007;Dakin & Montgomerie 2009;Bortolotti et al 2011) to increase their conspicuousness and/or colour contrast. There are also examples of how animals use behaviour, independent of environment, to increase their colour conspicuousness, such as animals covering/hiding colour patches and presenting them only in specific situations (Hansen & Rohwer 1986) or using displays to increase colour detection by catching the attention of the receiver (Ord & Stamps 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Per sensory drive model (Endler 1992), many environmental factors can influence colour-signal transmission and evolution, including water depth (Seehausen et al 2008) and vertical location in a forest (Endler 1993;Gomez & Thery 2004). Additionally, animals often interact with the environment by seeking out specific lighting conditions (Endler & Thery 1996;Heindl & Winkler 2003;Seehausen et al 2008;Cronin et al 2014;Simpson & McGraw 2018a) or orienting themselves in specific ways relative to the sun (Hamilton 1965;Rutowski et al 2007;Dakin & Montgomerie 2009;Bortolotti et al 2011) to increase their conspicuousness and/or colour contrast. There are also examples of how animals use behaviour, independent of environment, to increase their colour conspicuousness, such as animals covering/hiding colour patches and presenting them only in specific situations (Hansen & Rohwer 1986) or using displays to increase colour detection by catching the attention of the receiver (Ord & Stamps 2008).…”
Section: Introductionmentioning
confidence: 99%
“…; Cronin et al . ; Simpson & McGraw ) or orienting themselves in specific ways relative to the sun (Hamilton ; Rutowski et al . ; Dakin & Montgomerie ; Bortolotti et al .…”
Section: Introductionmentioning
confidence: 99%
“…; Endler et al. ; Simpson and McGraw ). Although these studies have revealed important evolutionary links between environmental/nonsignaling traits and animal signals, questions remain about how and why certain signals coevolve together (or antagonistically).…”
Section: A List Of Color Variables and Mismatch Methods Used Throughomentioning
confidence: 99%
“…Thus, the ecological divergence between populations arises due to habitat structure, climate, resource differences and the presence of both predators and competitors [2,4]. In birds, studies that show divergent ecologies acting on colour, morphology and song [5,6] refer to Gloger's, Bergmann's and Allen's rules for morphological traits or the acoustic adaptation hypothesis for vocalizations to explain geographical patterns of phenotypic variation (e.g. [7][8][9][10][11]).…”
Section: Introductionmentioning
confidence: 99%